Problematizing de Beauvoirs Myth of Woman through Gender Relation in David Lehmans When a Woman Loves a Man - Pramesthi Dewi Kusumaningrum; Sri Mulyani (Universitas Sanata Dharma, 2016)
Gender relation in society is complex and fluid. However, the complexity and fluidity are oversimplified by patriarchal systems in the form of binary oppositions. David Lehmans When a Woman Loves a Man is a poem portraying the complexity and fluidity of gender relation. Through several levels of reading the poem, gender relations between woman and man are proven to be dynamic, yet it is still dominated by patriarchal systems. This research attempts to problematize de Beauvoirs myth of woman which represents gender relation between woman and man in binary oppositions. This research applies deconstructive method. The deconstructive method includes close reading and deconstructive reading. It is applied to problematize de Beauvoirs myth of woman through Lehmans When a Woman Loves a Man. The first level of reading (close reading) in Lehmans When a Woman Loves a Man shows that the findings on the form, diction, word order, point of view, and tone versus the findings on metaphors, imagery, symbols, and allusions are contradictory. The second level of reading (explication) shows that Lehmans When a Woman Loves a Man depicts some gender relation. Those are woman- man relation in speaking, never being in the same domain, performing different roles in the same domain, communicating, viewing gender relation, fighting, and considering night and sleep. The last level of reading is deconstructive reading. The first level of deconstructive reading questions the objectivity of portraying woman-man relation. The second level reveals the discontinuity of de Beauvoirs myth of woman to construct the gender relation in the poem in binary oppositions. The universalizing context and the absence of womans voice in de Beauvoirs myth of woman reveal the question of the objectivity of the myth and how even though de Beauvoirs myth of woman stereotypes both genders unequally, woman remains the marginalized one. Keywords: myth of woman, gender relation, deconstructive reading.